Pengaruh Kewajiban Moral, Kualitas Pelayanan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak pada Kantor Pelayanan Pajak Pratama Makassar Selatan - Sari, Indah; Daud, Dahniyar; Ahmad, Ruslan (Al-Buhuts, 2024)
This study aims to find out how moral obligations, service quality and tax penalties affect taxpayer compliance at the South Makassar Pratama tax office. Data collection using primary data obtained from questionnaires using sample techniques based on the Slovin formula. The population is 199.177 taxpayers at South Makassar Primary Tax Office, with a total of 100 respondent taxpayers. Data analysis in this study uses multiple regression analysis. The results showed a positive and significant hypothesis. This means that moral obligations, service quality and tax penalties have a positive and significant effect on taxpayer compliance